2017
DOI: 10.1155/2017/6180636
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Gliricidia sepium Biochar on Attenuate Perchlorate-Induced Heavy Metal Release in Serpentine Soil

Abstract: Perchlorate (ClO4-) is a strong oxidizer, capable of accelerating heavy metal release into regolith/soil. Here, we assessed interactions between ClO4- and serpentine soil to simulate and understand the fate of Ni and Mn and their immobilization with the presence of biochar (BC). A soil incubation study (6 months) was performed using serpentine soil in combination with different ClO4- concentrations (0.25, 0.5, 0.75, and 1 wt.%) and three different amendment rates (1, 2.5, and 5 wt.%) of Gliricidia sepium BC. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 43 publications
(54 reference statements)
1
3
0
1
Order By: Relevance
“…(SP, incubated at saturated point; FC, incubated at field capacity; SP-PW, incubated at saturated point followed by permanent wilting point; and FC-PW, incubated at field capacity followed by permanent wilting point) were 2.007, 7.581, 0.005, and 5.900% of the total metal concentration, respectively. The findings of Kumarathilaka and Vithanage (2017) reflect a similar tendency as bioavailable Ni and Mn concentrations of serpentine soils were 0.30 and 0.25%, respectively, of total concentrations. Moreover, 33-323 and 11-76 mg kg −1 of Ni and Mn, respectively, were found as bioavailable fractions from four serpentine localities in Sri Lanka (Vithanage et al 2014).…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…(SP, incubated at saturated point; FC, incubated at field capacity; SP-PW, incubated at saturated point followed by permanent wilting point; and FC-PW, incubated at field capacity followed by permanent wilting point) were 2.007, 7.581, 0.005, and 5.900% of the total metal concentration, respectively. The findings of Kumarathilaka and Vithanage (2017) reflect a similar tendency as bioavailable Ni and Mn concentrations of serpentine soils were 0.30 and 0.25%, respectively, of total concentrations. Moreover, 33-323 and 11-76 mg kg −1 of Ni and Mn, respectively, were found as bioavailable fractions from four serpentine localities in Sri Lanka (Vithanage et al 2014).…”
Section: Discussionsupporting
confidence: 69%
“…Biochar, a type of black carbon resulting from pyrolysis of biomass under no/limited oxygen conditions, has been proven to be an effective and low-cost organic amendment for trace metal-contaminated sites (Inyang et al 2016). Previous research of our group has revealed strong immobilization capacity of 2.5% dendro-biochar (Gliricidia sepium biochar) on trace metals released from serpentine soils (Herath et al 2015; Kumarathilaka and Vithanage 2017). Herath et al (2015) found that dendro-biochar reduces bioavailable Cr, Ni, and Mn in serpentine soil by 96, 36, and 21%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Immobilisation was attributed to the higher oak biochar pH and lower DOC concentrations (due to biochar surface sorption). Similarly, bioenergy waste biochar reduced bioavailability of Ni (68-92%) and Mn (76-93%) (Kumarathilaka and Vithanage 2017). The immobilisation of these HMs was due to surface diffusion and electrostatic attractions.…”
Section: Soil Physicochemical Propertiesmentioning
confidence: 97%
“…Char derived from the paper and plastic waste mixture showed the highest capacity of 172 µg g −1 [37]. The impact of char on the release rate of certain trace metals in soils contaminated with organic and inorganic acids was assessed in two studies [72,73]. The addition of woodchips GC to the contaminated soil reduced the bioavailability of Ni and Mn, and reduced the Pb and Cu release rate to the soil.…”
Section: Gas Adsorption and Soil Remediationmentioning
confidence: 99%